2015
DOI: 10.7166/26-1-1022
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Direct Metal Laser Sintered Ti-6al-4v

Abstract: Direct metal laser sintering (DMLS) is a selective laser melting (SLM) manufacturing process that can produce near net shape parts from metallic powders. A range of materials are suitable for SLM; they include various metals such as titanium, steel, aluminium, and cobalt-chrome alloys. This paper forms part of a research drive that aims to evaluate the material performance of the SLM-manufactured metals. It presents DMLS-produced Ti-6Al-4V, a titanium alloy often used in biomedical and aerospace applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 21 publications
2
24
0
2
Order By: Relevance
“…It has previously been reported that SLM-produced Ti-6Al-4V comprises martensitic microstructures with evidence of acicular α' phases and no β phase [13,18,20,16]. Given that this starting microstructure is vastly different from conventional forms, standard heat treatments will not necessarily provide the desired result.…”
Section: Heat Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been reported that SLM-produced Ti-6Al-4V comprises martensitic microstructures with evidence of acicular α' phases and no β phase [13,18,20,16]. Given that this starting microstructure is vastly different from conventional forms, standard heat treatments will not necessarily provide the desired result.…”
Section: Heat Treatmentmentioning
confidence: 99%
“…In particular, the fast cooling rates and layer-wise building in the LaserCUSING process result in a fine, non-equilibrium phase and anisotropic behaviour [16][17][18][19][20]. This martensitic microstructure manifests in high hardness and high strength/low ductility material behaviour, requiring the use of heat treatments to obtain a balance of properties similar to those of the bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…The process uses a scanning laser beam to form three dimensional objects in a layer-upon-layer build-up, based on three-dimensional computer aided design (CAD) model data input [3]. DMLS of Ti6Al4V is increasingly used in the biomechanical, aerospace, and automotive industries because of its ability to produce custom geometrically complex designs to high tolerances and with minimal material waste [4]. Ti6Al4V is used in the aforementioned industries because it is corrosion resistant, has a good strength-to-weight ratio and is bio-compatible [5,6].…”
Section: Sources Of Fatigue Failure In As-built Dmls Of Ti6al4v (Eli)mentioning
confidence: 99%
“…A large degree of shrinkage occurs during liquid -solid transformation, thus accumulating considerable tensile residual stresses on the surface of the SLM produced components. The complex residual stresses (RS) that arise during cooling are regarded as key factors responsible for the distortion and even delamination of the final parts [9,10,[15][16][17]. These residual stresses may even cause process failure during the building phase [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, although the mechanical properties have become close to those of bulk materials [3][4][5][6][7][8][9][10][11][12][13][14], SLM has some inherent drawbacks such as warping, cracking and detrimental tensile residual stresses (TRS). A large degree of shrinkage occurs during liquid -solid transformation, thus accumulating considerable tensile residual stresses on the surface of the SLM produced components.…”
Section: Introductionmentioning
confidence: 99%